Chromaticity coordinate vector principle for charge-transfer-type thermochromic material design: case of Fe/Cr-(co)doped α-Al2O3 host. Issue 31 (26th July 2022) - Zhang, Wen; Xu, Hongda; Wang, Shan; Fang, Hairui; Li, Tianyi; Zhang, Yumei; Li, Dongfei; Meng, Xiangdong; Hou, Changmin; Yuan, Long
Abstract : Chromaticity coordinate vector principle is demonstrated in the design of charge-transfer-type inorganic thermochromic materials for the first time. Abstract : Charge-transfer-type thermochromic materials have gained increasing research interest due to their smart character of continuous reversible color change with temperature. However, the interaction between different chromophores in the same host matrix and the underlying mechanism have not been elucidated. Herein, we propose a chromaticity coordinate vector principle in a model system of α-Al2 O3 as the host and Cr 3+ and Fe 3+ as chromophore probes to illustrate the interaction effect of different inorganic chromophores on the thermochromic behaviour of materials. Single chromophores of Fe 3+ and Cr 3+ with different doping compositions were assessed firstly to acquire their basic thermochromic behaviour. Then, samples containing both Fe 3+ and Cr 3+ with varying stoichiometry were prepared to assess the thermochromic contribution of each chromophore. The phase purity and structural evolution with different doping species and compositions were analysed via Rietveld refinement of the powder X-ray diffraction data and vibration spectroscopic techniques. Also, the chromaticity coordinates of samples as a function of temperature were recorded. The color of Al2− x Fe x O3 showed a continuous change from slight yellow to bright orange with an increase in x from 0.10 to 0.32, which is ascribed to the increase in the internal band optical transition of 3d-electrons in the octahedral field. The color of Cr-doped materials showed a purple to green color transition either by increasing the doping level or heating up to 550 °C with a composition-dependent color transition at doping-level dependent temperature points. For the Fe, Cr-co-doped samples, the color gradually changed from light yellowish brown to dark brown with an increase in the Fe doping amount. When keeping the Fe-amount constant, by increasing the Cr-doping amount, the color of the samples gradually changed from khaki to dark brown. All the thermochromic vectors of the a *-parameter follow the typical vector calculation principle for the Fe-doped, Cr-doped, and Fe, Cr-co-doped materials with nominal stoichiometric relationships, except for the highly doped samples ( i.e., for the compositions of x ≥ 0.28 and y ≥ 0.40), which can be ascribed to the phase segregation. The proposed temperature-chromaticity coordinate vector relationships for different chromophores in the common host matrix provide a fundamental design and fabrication principle for charge-transfer-type thermochromic materials.